Psychological Skills during Training and Competition on Recovery-Stress State among Adolescent State Athletes - Kuan, Garry; Kueh, Yee-Cheng (Journal of Sports Research, 2015)
The relationship between self-report psychological skills and recovery-stress state was investigated. Seventy adolescent state athletes in Malaysia completed the Test of Performance Strategies (TOPS), and Recovery-Stress questionnaire (RESTQ-Sport). Correlation analysis was used to determine the significant relationship between the psychological skills and recovery-stress subscales. The results showed that there were significant correlations between the psychological skills and recovery-stress states. For psychological skills during practice, the strongest correlations were observed in attention control and general stress (r = -0.48, p < 0.01), goal setting and total recovery (r = 0.72, p < 0.01), and psychological skills during competition, the strongest correlations were observed in self-talk and general stress (r = -0.55, p < 0.01), goal setting and total recovery (r = 0.57, p < 0.01). The direction (positive or negative) of correlations showed that individuals reporting frequent use of psychological skills also reported lower state of stress and higher state of recovery in their sport during practice and competition. Future researchers should seek to establish the path relationships by investigating whether demographic variables, physical fitness level and other psychological measures that may associated with recovery-stress states and the use of psychological skills for athletes.